A robust esterified nanofibre electrode for proton exchange membrane fuel cells. Issue 10 (28th February 2020) - Qi, Manman; Hou, Ming; Zeng, Yachao; Gao, Yanyan; Yang, Yue; He, Liang; Chen, Haiping; Zhang, Hongjie; Song, Wei; Shao, Zhigang
Abstract : An esterified nanofibre electrode with enhanced dimensional stability has been proposed for proton exchange membrane fuel cells. Abstract : Optimizing the architecture of cathodic catalyst layers is significant in improving the catalyst utilization and enhancing the performance and durability of proton exchange membrane fuel cells (PEMFCs). Nanofibre electrodes possess continuous proton and electron transport channels, and are advantageous over conventional electrodes for mass transport. However, the structural stability of the nanofibre electrodes has been rarely reported in the literature. Herein, a highly stable esterified nanofibre electrode was prepared by esterifying poly (acrylic acid) (PAA) with poly (vinyl alcohol) (PVA) to address the structural stability of the nanofibre electrodes during the operation of PEMFCs. Both the ex situ and in situ tests confirm that the esterified nanofibre electrode has enhanced structural stability compared with conventional nanofibre electrodes. The concept of an esterified nanofibre electrode inspires a facile approach for stabilizing polymer binders in fuel cell catalyst layers, especially for nanofibre electrodes.